Investigating Innovative Experimental Curricular Approaches to Enhance Conceptual Development in Mathematics Education - Enti Mensah, Louis; Asamoah , Emmanuel; Antwi , Richmond; Owusu, Daniel (International Journal of Mathematics and Mathematics Education (IJMME), 2025)
Purpose  – Mathematics education is increasingly shifting from rote memorization to approaches that foster conceptual understanding. In Ghana, however, traditional methods still dominate, limiting students' ability to apply mathematical concepts effectively. This study investigates the impact of active learning strategies—Problem-Based Learning (PBL), Inquiry-Based Learning (IBL), manipulatives, and technology integration—on students’ conceptual understanding of mathematics within a sub-Saharan African context. Methodology – A quantitative design was employed, involving 300 students from the Ejisu-Juaben Municipality in Ghana, selected through stratified random sampling. Data were collected using structured questionnaires and analyzed statistically to assess the relationship between instructional strategies and conceptual learning outcomes. Findings – The results indicate that technology integration had the strongest positive effect on students’ comprehension and engagement. PBL also improved learning outcomes but required additional instructional support. Both IBL and the use of manipulatives contributed moderately to conceptual understanding. Novelty – This study offers a novel contribution by addressing an underrepresented region in educational research. It is among the first to examine the combined effects of multiple active learning strategies in a sub-Saharan African setting, with a specific focus on conceptual understanding rather than performance metrics. Significance – The findings provide actionable insights for educators and policymakers in developing contexts, emphasizing the importance of adopting technology-enhanced and student-centered approaches to improve mathematics instruction and deepen students’ problem-solving abilities.